Associação de gabapentina como adjuvante à raquianestesia para controle da dor aguda em colecistectomia convencional - Poma, Mara Aparecida Maricato (2015)
The cholelithiasis is the main biliary tract disease that affects a significant amount of the population, an issue of global public health. In Brazil, is the most common surgical abdominal disease, with about 200,000 hospitalizations annually by the Unified Health System (SUS). The treatment is surgical and can be done conventionally or laparoscopic surgery, the is gold standard option. But the reality of our public health system shows that the vast majority of surgical procedures performed are conventional cholecystectomy. What demand the need for appropriate anesthetic management for effective, safe anesthesia, with control of neuro endocrine response to trauma and postoperative pain. The objective of this clinical study, prospective, double-blind randomly distributed was to evaluate the use of gabapentin by mouth as an adjunct to spinal anesthesia for acute pain control in conventional cholecystectomy. We selected 59 patients with cholelithiasis for elective surgery in general surgery service of Hospital Santa Casa de Misericordia de Fortaleza, being divided into two groups: Gabapentin group (GGP), gabapentin was administered in 31 patients in the 600mg via dose oral 01 hour before surgery and the second control group (CG) were administered placebo, 1 tablet 01 hour before surgery in 28 patients. Both groups underwent spinal anesthesia with sufentanil for performing conventional cholecystectomy. The main variables were: age, gender, heart rate, systolic and diastolic blood pressure, glucose levels, pain scores and morphine consumption postoperatively. The results showed no statistically significant differences between the gabapentin group and the control group.We conclude that the use of gabapentin by mouth as an adjunct to spinal anesthesia in conventional laparoscopic not interfere with the hemodynamic response during surgery or in the control of acute postoperative pain, no consumption of morphine, either on the glycemic index in the post-period operatively.